Cultivating an organizational effort for development. Issue 2 (8th August 2016) - Crumpton, Michael A.
Abstract : Purpose: This paper aims to explore the concept of providing education and guidance to library staff for the purpose of supporting philanthropic activities made on behalf of the library. The need for this type of activity and basic principles of philanthropy are included. Design/methodology/approach: This paper includes a through literature review and a case study narrative with examples on activities at the author's home institution. Findings: The literature supports that cultivating a broader, more detailed understanding of philanthropic activities within the organization, will improve fundraising results and individual satisfaction for giving and receiving. Practical implications: The concepts discussed have beginnings in other institutions and recognize a trend of adapting business models to libraries' needs. Originality/value: The is the author's own work, shared with members of the author's organization.